The Effects of Operational Conditions in Scaling Up of Xylanase Enzyme Production for Xylitol Production - Diah Meilany; Dewinka Anugeraheni; Abdul Aziz; Made Tri Ari Penia Kresnowati; Tjandra Setiadi (Dept. of Chemical Engineering, Diponegoro University, 2020)
The biological route to produce xylitol from Oil Palm Empty Fruit Bunches (EFBs) comprises of EFBs pretreatment, enzymatic hydrolysis, fermentation, and downstream separation of the produced xylitol. Due to the specificity in the hemicellulose composition of EFBs, a xylanase enzyme that has a high affinity to EFBs is required to hydrolyze the EFBs into xylose. In this research, the influences of aeration, humidity, and mixing in xylanase production were mapped. The xylanase production was performed by Aspergillus fumigatus ITBCCL170 in a solid-state fermentation using a tray fermenter with EFBs as the substrate. The optimal configuration was further scaled up into xylanase production using 1000 g of EFBs as the substrate. The results showed that the highest enzyme activity was 236.3 U/g EFB, obtained from the use of humid air airflow of 0.1 LPM, and mixing was performed once a day. The scaling up resulted in a lower xylanase activity and call for a better design of the fermenter.Keywords: aeration, humidity, mixing, OPEFBs, tray fermenter, xylanase, xylitol